1999
DOI: 10.3354/ame020083
|View full text |Cite
|
Sign up to set email alerts
|

Mixotrophic and heterotrophic nanoflagellate grazing in the convergence zone east of New Zealand

Abstract: Nanoflagellate grazing was investigated in the subtropical convergence region off the east coast of the South Island, New Zealand, in the summer of 1995. Clearance rates were estimated using 0.5 pm fluorescently labelled beads and fluorescently labelled bacteria to represent bacterial populations and 1.0 pm fluorescently labelled beads representing picophytoplankton populations. Nanoflagellate grazing by mixotrophs was on average lower than heterotrophic nanoflagellate clearance rates per individual for all pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 38 publications
5
31
2
Order By: Relevance
“…For instance, Leakey et al (1996) reported that 9 to 33% of the BP was grazed daily by HNF in the Ross Sea, Antarctica. Safi & Hall (1999) estimated that 40 to 55% of the bacterioplankton standing stock was grazed by MNF, whereas Christaki et al (1999) reported that ~40% BP d −1 was grazed by HNF and only 5% BP d −1 by MNF. Similar to these reports, bacterivory in our study also appeared to be dominated by HNF rather than MNF.…”
Section: Mixotrophic Nanoflagellates In Carbon and Food Web Models Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Leakey et al (1996) reported that 9 to 33% of the BP was grazed daily by HNF in the Ross Sea, Antarctica. Safi & Hall (1999) estimated that 40 to 55% of the bacterioplankton standing stock was grazed by MNF, whereas Christaki et al (1999) reported that ~40% BP d −1 was grazed by HNF and only 5% BP d −1 by MNF. Similar to these reports, bacterivory in our study also appeared to be dominated by HNF rather than MNF.…”
Section: Mixotrophic Nanoflagellates In Carbon and Food Web Models Ofmentioning
confidence: 99%
“…However, the use of similar FLB uptake measurements in more oligotrophic environments (Aegean Sea, NW Mediterranean Sea, East New Zealand) has revealed larger MNF abundances, from 200 to 3000 cells ml −1 (e.g. Christaki et al 1999, Safi & Hall 1999, Unrein et al 2007). …”
Section: Relative Importance Of Different Nanoflagellate Forms Under mentioning
confidence: 99%
“…First, the formation of freshwater cap might inhibit the migration of mesozooplankton (e.g. copepods) into the water with lower salinity and change the mesozooplankton composition in the water column in the studied waters, as similar salinity effects on mesozooplankton have been observed in estuarine and inshore waters (Grindley, 1964;Zhou et al, 2015b), which can release the mesozooplankton grazing pressure on ciliates, then through trophic cascades increase the ciliate grazing on nanoflagellates (HNF) (Chen et al, 2012), reducing the abundance of HNF -the main grazer on pico-phytoplankton (Safi and Hall, 1999) -and releasing the grazing pressure on picophytoplankton (Klauschies et al, 2012). Second, as discussed above, the impeding effect of freshwater cap on phytoplankton accesses to nutrients could lead to poor food quality of phytoplankton as prey, and thus reduce the grazing activity of microzooplankton.…”
Section: East Asian Monsoon Influencing Seasonal Variations In Phytopmentioning
confidence: 99%
“…In fact, they have been observed as major picoplankton grazers in a variety of environments. Havskum and Riemann (1996) calculated that mixotrophs were responsible for up to 86% of the total bacterial grazing in some coastal environments, whereas Safi and Hall (1999) estimated a contribution of 55% in the subtropical convergence east of New Zealand. In some freshwater lakes mixotrophs may remove more bacteria than the crustacean, rotifer, and ciliate communities combined (Bird and Kalff 1986).…”
mentioning
confidence: 99%